A balance between TFPI and thrombin-mediated platelet activation is required for murine embryonic development - Ellery, Paul; Maroney, S.; Cooley, B.; Luyendyk, J.; Zogg, M.; Weiler, H.; Mast, A. (American Society of Hematology, 2015)
Tissue factor pathway inhibitor (TFPI) is a critical anticoagulant protein present in endothelium and platelets. Mice lacking TFPI (Tfpi−/−) die in utero from disseminated intravascular coagulation. They are rescued by concomitant tissue factor (TF) deficiency, demonstrating that TFPI modulates TF function in vivo. Recent studies have found TFPI inhibits prothrombinase activity during the initiation of coagulation and limits platelet accumulation during thrombus formation, implicating TFPI in modulating platelet procoagulant activity. To examine whether altered platelet function would compensate for the lack of TFPI and rescue TFPI-null embryonic lethality, Tfpi+/− mice lacking the platelet thrombin receptor, protease activated receptor 4 (PAR4; Par4−/−), or its coreceptor, PAR3, were mated. PAR3 deficiency did not rescue Tfpi−/− embryos, but >40% of expected Tfpi−/−:Par4−/− offspring survived to adulthood. Adult Tfpi−/−:Par4−/− mice did not exhibit overt thrombosis. However, they had focal sterile inflammation with fibrin(ogen) deposition in the liver and elevated plasma thrombin-antithrombin complexes, indicating activation of coagulation at baseline. Tfpi−/−:Par4−/− mice have platelet and fibrin accumulation similar to Par4−/− mice following venous electrolytic injury but were more susceptible than Par4−/− mice to TF-induced pulmonary embolism. In addition, ∼30% of the Tfpi−/−:Par4−/− mice were born with short tails. Tfpi−/−:Par4−/− mice are the first adult mice described that lack TFPI with unaltered TF. They demonstrate that TFPI physiologically modulates thrombin-dependent platelet activation in a manner that is required for successful embryonic development and identify a role for TFPI in dampening intravascular procoagulant stimuli that lead to thrombin generation, even in the absence of thrombin-mediated platelet activation.